IMPLEMENTASI UNDANG- UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK DALAM UPAYA MELINDUNGI KEPENTINGAN ANAK - Varida Ariani, Nevey (Jurnal Media Hukum, 2014)
ChildrenÂ  areÂ  a mandateÂ  from God Almighty whichÂ  inÂ  themÂ  laidÂ  aÂ  dignityÂ  as humanÂ  beings.Â  ChildrenÂ  need protection against negative effects of a fast-growing developmnet. This essay is trying to discuss about howâs theÂ  implementation ofÂ  theÂ  lawÂ  ofÂ  SPPAÂ  andÂ  theÂ  Government ofÂ  IndonesiaâsÂ  effortsÂ  in protectingÂ  children especially those who are conflicted with the law in accordance to The Law number 11 Year 2012. The method applied in this essay is qualitative socio-legal approach, based on theÂ  library data. In the investigation process, prosecutionÂ  untilÂ  theÂ  proceedings,Â  thereÂ  stillÂ  be diversionÂ  processÂ  IsÂ  ultimatelyÂ  enforcedÂ  consideringÂ  the childrenâs age and the penalties are not over than 7 years.Â  If this diversion processÂ  is not applicableÂ  then the judicial process is becoming ultimum remedium, putting the children in LPAS, LPAK and LPKS. Those institutions areÂ  expectedÂ  to giveÂ  new hopesÂ  toÂ  children whoâs dealing withÂ  theÂ  legal matters.Â  ThroughÂ  theÂ  approching systemÂ  inÂ  JuvenileÂ  CriminalÂ  CourtÂ  ProcessÂ  fromÂ  investigators, prosecutors,Â  judges,Â  advocatesÂ  toÂ  theÂ  public counselor, bothÂ  the Ministry ofÂ  LawÂ  and Human Rights andÂ  theÂ  Social Ministry,Â  itÂ  isÂ  necessaryÂ  to establishÂ  a clearÂ  coordinationÂ  andÂ  roleÂ  inÂ  implementingÂ  theÂ  Juvenile Criminal CourtÂ  System.